The asymmetric behavior and procyclical impact of asset correlations - Lee, Shih-Cheng; Lin, Chien-Ting; Yang, Chih-Kai (Journal of Banking & Finance, 2011)
This paper examines the behavior of asset correlations with the market returns in the asymptotic single risk factor (ASRF) approach of the Basel II accord on regulatory capital requirement. Over a sample period from 1988 to 2007, we find that asset correlations are positively related to firm size, but negatively related to firm default probability. Asset correlations are also industry specific, as firms in media, transportation, pharmaceutical, and semiconductor industries exhibit higher asset correlations than those in retail and consumer staples. Most importantly, asset correlations are asymmetric and have a procyclical impact on the real economy after controlling for these effects. They tend to rise during economic downturns, but decline during economic upturns. The average magnitude of the rise is larger than that of the decline. These findings suggest that asset correlations may be underestimated during economic downturns, and may provide policy implications for the capital requirement framework.